2013
DOI: 10.1007/s00380-013-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ventricular fibrillation by electrical modification of the Purkinje system in hypertrophic cardiomyopathy

Abstract: A 56-year-old man in hypertrophic cardiomyopathy had an electrical storm caused by ventricular fibrillation (VF). Mapping during the initiation of the VF triggered by a premature ventricular contraction (PVC1), with right bundle branch block (RBBB)-like morphology and superior axis, demonstrated a prominent Purkinje-muscle junction (PMJ) delay at the distal portion of the left posterior fascicle. Delivery of radiofrequency (RF) energy to this area abolished the VF triggered by the PVC1. However, VF emerged by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…Catheter ablation is also useful to reduce the risk of recurrent VT compared with medical therapy alone [21][22][23][24]. However, there were no significant differences in the usage of anti-arrhythmic drugs and in the number of catheter ablation between the two settings in our report.…”
Section: Effects Of Treatment Changes During the Follow-upcontrasting
confidence: 70%
“…Catheter ablation is also useful to reduce the risk of recurrent VT compared with medical therapy alone [21][22][23][24]. However, there were no significant differences in the usage of anti-arrhythmic drugs and in the number of catheter ablation between the two settings in our report.…”
Section: Effects Of Treatment Changes During the Follow-upcontrasting
confidence: 70%
“…These novel findings suggest that shock reduction in patients after shock is important for not only quality of life but also prognosis. For this purpose, catheter ablation for VT and even VF may be promising [24][25][26][27][28]. The VANISH trial demonstrated that catheter ablation was superior to escalated antiarrhythmic drug therapy in terms of decrease in the primary composite outcome of death, VT storm, or appropriate ICD shock among patients with ischemic cardiomyopathy and an ICD who had VT despite the use of antiarrhythmic drugs [29].…”
Section: Discussionmentioning
confidence: 99%
“…RF was applied in this area as well, and the VF ended. Consequently, it has been reported that a delay of the Purkinje‐muscle junction and similar activity, such as Purkinje muscle reentry, is the source of a Purkinje‐related VF trigger …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been reported that a delay of the Purkinje-muscle junction and similar activity, such as Purkinje muscle reentry, is the source of a Purkinjerelated VF trigger. 7 Carbucicchio et al used an EA3DMS for an ablation application in 95 adult patients with an ICDS. The conditions included coronary artery disease in 76% of the patients, idiopathic dilated CM in 10% of the patients, and arrhythmogenic right ventricular dysplasia/cardiomyopathy in 14% of the patients.…”
Section: Discussionmentioning
confidence: 99%